Ekspektasi, Kebiasaan, Hedonisme, dan Biaya: Memahami Dinamika Minat Penggunaan QRIS di Kabupaten Mimika - Kusuma, Manggar Wulan; Novalia Herlina Susanti Kareth (Jurnal Ekonomi Dan Bisnis, 2024)
This study aims to determine the effect of performance expectations, habits, hedonic motivations, and transaction costs on the interest in using the Quick Response Indonesian Standard (QRIS) which is quantitative. This study used respondents from Mimika Regency residents, with the criteria of having an m-banking application and having used QRIS in making payments. The research method used is multiple linear regression analysis. The results of this study indicate that performance expectations, habits, hedonic motivations and transaction costs have a positive effect on the interest in using QRIS in the community in Mimika Regency. Based on the results of this study, we hope that the people of Mimika Regency can increase the use of non-cash transactions such as the use of QRIS as a means of payment.